Muscle biopsy findings, conduction velocity and refractory period of single motor nerve fibres in schizophrenia. - Borg, J (1987)
Eight untreated and eight neuroleptic treated male schizophrenic patients were studied. Light and electron microscopical analysis of muscle biopsies from the anterior tibial muscle showed a spectrum of pathological changes without significant quantitative or qualitative differences between the two groups. The changes included atrophic fibres, central nuclei, "moth-eaten fibres", "ring fibres", fibre splitting and subsarcolemmal and intermyofibrillar glycogen droplets. Electrophysiological investigation of single motor unit properties showed impaired peripheral impulse propagation in both patient groups while the conduction velocity and the refractory period of single motor nerve fibres were within the same range as in healthy subjects. In conclusion there are neuromuscular abnormalities in schizophrenic patients which cannot be attributed to medication or drug abuse.